2002
DOI: 10.1104/pp.010889
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tryptophan Decarboxylase to Selected Subcellular Compartments of Tobacco Plants Affects Enzyme Stability and in Vivo Function and Leads to a Lesion-Mimic Phenotype

Abstract: Tryptophan decarboxylase (TDC) is a cytosolic enzyme that catalyzes an early step of the terpenoid indole alkaloid biosynthetic pathway by decarboxylation of l-tryptophan to produce the protoalkaloid tryptamine. In the present study, recombinant TDC was targeted to the chloroplast, cytosol, and endoplasmic reticulum (ER) of tobacco (Nicotiana tabacum) plants to evaluate the effects of subcellular compartmentation on the accumulation of functional enzyme and its corresponding enzymatic product. TDC accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 54 publications
(22 reference statements)
3
32
0
Order By: Relevance
“…TDC activity was about 2-fold higher in the roots than in the shoots and ranged from 0.36 to 1.83 pkat mg 21 protein, which was consistent with the values reported by Lopez-Meyer and Nessler (1997) and Ueno et al (2003). As for a negative control of TDC assay, we employed tobacco, which was reported to lack TDC gene (Fiore et al, 2002). TDC activities from leaves and suspension-cell culture of tobacco were not detected at all.…”
Section: Serotonin Derivatives In Transgenic Rice Plantssupporting
confidence: 86%
“…TDC activity was about 2-fold higher in the roots than in the shoots and ranged from 0.36 to 1.83 pkat mg 21 protein, which was consistent with the values reported by Lopez-Meyer and Nessler (1997) and Ueno et al (2003). As for a negative control of TDC assay, we employed tobacco, which was reported to lack TDC gene (Fiore et al, 2002). TDC activities from leaves and suspension-cell culture of tobacco were not detected at all.…”
Section: Serotonin Derivatives In Transgenic Rice Plantssupporting
confidence: 86%
“…Based on extensive pathogen testing, we have concluded that these lesions are not associated with disease. Similar lesion mimic phenotypes have been observed in a variety of transgenic plants in which antioxidant levels (Takahashi et al, 1997), carbohydrate metabolism (Mittler and Rizhsky, 2000), defenseassociated genes (Shirano et al, 2002), or phenolic metabolism (Di Fiore et al, 2002) have been manipulated. The absence of elevated reactive oxygen species levels, SA, and oxidative damage in PPO-silenced lines points to a subtle, potentially metabolic, connection between cell death and PPO in walnut.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, targeting enzymes to an atypical subcellular compartment provides a novel strategy for creating additional capacities for rate-limiting steps of a pathway. The feasibility of such a strategy has been illustrated for the biosynthesis of amino acids [14,15] and terpenoid indole alkaloids in plants [16]. In the presented study, we demonstrated that targeting of recombinant ODC to a different and atypical subcellular compartment resulted in significant increased enzyme activity and putrescine levels.…”
Section: Introductionmentioning
confidence: 60%